Implementasi Nilai-Nilai Religius dalam Musik Gambus Melayu Riau - Laila Fitriah; Evadila Evadila; Idawati Idawati; Nussy Anggraini (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2022)
The development of science and technological progress as it currently has such a large impact on character values, religious values, social values, customs and value systems that exist in society. This situation has a negative impact on the younger generation due to not being able to respond properly. The application of religious values ​​is the main capital in dealing with the negative impacts of technological progress. Through art education with Gambus art media, religious values ​​can be realized for the younger generation. This study aims to explain the religious values ​​that exist in the Riau Malay Gambus art. This research was conducted in Pekanbaru City, Riau, the research subjects were students of the Sendaratasik Department of the Islamic University of Riau and the object of research was the Riau Malay Gambus art. This type of research is descriptive qualitative research. The data collection method used is by conducting observations, interviews, literature studies and documentation. Data analysis will use descriptive qualitative method obtained from primary and secondary data. The results of this study indicate that in Riau Malay Gambus art there are religious values ​​such as the value of worship, the value of jihad (ruhul jihad), the value of morals and discipline and the value of exemplary. The most important religious value is the value of worship, because in Gambus art there are many lessons and messages that can be learned from the art, because the initial function of Gambus art itself is as a propaganda medium which contains many religious elements and messages for everyday life. day that can be realized in the midst of family and society. By itself the religious values ​​contained in Gambus art can be applied to today's young generation to avoid negative things that will happen.